Contraceptive use and preferences of young married women in Kerala, India - Thulaseedharan JV (Dove Medical Press, 2018)
Jissa Vinoda Thulaseedharan Achutha Menon Center for Health Science Studies (AMCHSS), Sree Chitra Tirunal Institute for Medical Sciences and Technology (SCTIMST), Trivandrum, Kerala, India Background: As in other states of India, female sterilization is the most widely used contraceptive method in Kerala where women have higher levels of education compared to most other states in India. This paper describes the use and preferences of contraceptive methods among young married women in Trivandrum district, Kerala, India.Subjects and methods: A community-based cross-sectional survey was carried out among 203 young married women (18–28 years) during January–March 2015 using multistage cluster sampling method. Statistical analysis was mainly descriptive, and chi-squared test was used to test the statistical significance of the relationship between sociodemographic factors and contraceptive use.Results: The average age at marriage for women was 21.3 years, and 23% of women had more than one child. Current use of any contraceptive methods was 58%. Female sterilization was preferred by 13% and it was significantly higher among women aged 25–28 years than in those aged 18–24 years (20% vs 2.6%, p<0.001). Female sterilization was significantly lower among women with higher levels of education than in women with an education level of plus two or below (5.8% vs 19%, p=0.006). Women were mostly in favor of female sterilization (91%), and a significantly lower proportion of highly educated women preferred female sterilization than women with an education of 12 years or below (85% vs 95.7%, p=0.008). Conclusion: A considerable number of females in the age group 25–28-years opting for sterilization and the unique preference for female sterilization when the family size is complete show the predominant reliance on female sterilization among young women. Higher education delays sterilization in young women due to delayed marriage and childbirth. Women empowerment, proper information and assuring availability and accessibility to different methods can gradually change the dominant preference for female-oriented permanent method of contraception. Keywords: contraception, female sterilization, Trivandrum, contraceptive preferences